Physiotherapy in contemporary higher vocational education - Jovanović, Stevan S.; Stojanović Jovanović, Bljana N. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2021)
In the last fifty years there has been a dramatic development and changes in all segments of the biomedical sciences which contributed to the development of expertise in the field of physiotherapy. In the description of the competence of the modern physiotherapists are numerous and complex skills such as clinical reasoning, the use of evidence-based practice, teamwork and interdisciplinary collaboration, health promotion and problem solving chronic diseases. As a research-based practice, physiotherapy uses facts, theories and hypotheses and test them on the available data. In 2014, the first cycle of higher education reforms was completed with the introduction of future vocational master. While the aim of the first higher education cycle is training for basic skills required for independent practice in the context of professional activities, second education cycle should provide training for students in planning processes, projects, decision making, development of leadership skills, with the assessment process, as well as additional of special physiotherapy knowledge and skills in selected areas and the knowledge of the so-called modern physical therapy technologies. A special segment of deepening skills during the second cycle of higher education and training is certainly for a higher level of professional functioning in interdisciplinary medical rehabilitation teams. Flexibility and adaptability are characteristics that a modern master degree programs should have. The formation and organization of joint master study programs in the fields of health science related to the physiotherapy can be very interesting organizational model for institutions of higher vocational education. This can be achieved by a greater degree of flexibility and adaptability of programs to the specific needs of students that stimulates the horizontal mobility of students within the European higher education area. The development of the physiotherapy profession in Europe and the world was marked by a significant increase in the volume of knowledge and skills, so the World Confederation for Physical Therapy and its European region, developed a strategy according to which are necessary all three cycles of higher education. Master vocational programs have 120 credits, so master professional titles in the future should provide access to doctoral studies.
Keywords: physiotherapy; evidence-based practice; modern vocational highеr education; vocational master studies; knowledge and skills